The changes in chemical properties of coffee during roasting: A review - Tarigan, E. B.; Wardiana, E.; Hilmi, Y. S.; Komarudin, N. A. (IOP Publishing Ltd, 2022)
Due to its chemical compounds, coffee has a good taste, pleasant aroma, stimulant effect, and health benefits. Roasting is a critical process to develop a good flavor and cup quality of the coffee brew. This article reviews the coffee chemical reaction proceeds during roasting, evaluates the roasted degree by physic and chemical approach and biochemical changes. The articles were compiled from ScienceDirect, SpringerLink, ResearchGate, and Google Scholar. Out of all of the collected papers, 40 articles were covered in this paper. The initial process of roasting is water content evaporating and continuously is followed by roasting phase including pyrolysis, Maillard reaction and caramelization. The roasted coffee degree is determined by visual, weight loss, acidity, and pop beans sound. The bioactive compounds of coffee such as chlorogenic acids, caffeine, and trigonelline affect brewed coffee's cup quality. Chlorogenic acid and trigonelline significantly decrease during the roasting process. However, caffein is quite stable during roasting. The roasted coffee performs a function in the consumers' health since in vitro and in vivo analysis present that bronze roasted espresso has the most powerful activity as anti-inflammatory and antioxidant. © Published under licence by IOP Publishing Ltd.